Locally Delivered Umbilical Cord Mesenchymal Stromal Cells Reduce Chronic Inflammation in Long-Term Nonhealing Wounds: A Randomized Study - Yulia Suzdaltseva; Sergey Zhidkih; Sergey L. Kiselev; Victor Stupin (Hindawi Limited, 2020)
Inflammation is part of a complex biological response to injury that mediates a rapid mobilization of cells and triggers the restoration of tissue homeostasis. The systemic diseases of the connective tissues, repetitive strain injuries, neuropathy, and vascular impairment lead to the development of a chronic inflammatory state. In such cases, a forced intervention is required to trigger tissue regeneration. Mesenchymal stromal cells (MSCs) have been considered a perspective tool for regenerative medicine because of their ability to change the expression and secretory profile under the influence of signals from the microenvironment to perform a regulatory function at the site of tissue damage. In this study, MSCs were isolated from the human umbilical cord (UCMSCs). The ability of UCMSCs to regulate chronic inflammation was investigated in a randomized placebo-controlled pilot study to assess the efficacy and safety of UCMSC therapy in patients with nonhealing wounds. A total of 108 patients with chronic wounds of different etiologies were randomly divided into two groups according to the criteria of inclusion and exclusion. The group (n=59) that was treated with a single local subcutaneous infusion of UCMSCs around the wound periphery showed a pronounced growth of granulation tissue, improved blood microcirculation, and reduction in wound size compared to the placebo group (n=49). No prominent adverse events were detected in patients from the UCMSC group during the 1-year follow-up period. This research has demonstrated that locally delivered allogeneic UCMSCs can contribute to chronic wound repair and provide an additional support toward new therapeutic strategies. Registration certificate №FS2006/341 was issued by the Federal Service for Surveillance in Healthcare.